2022
DOI: 10.1021/acs.jmedchem.2c00640
|View full text |Cite
|
Sign up to set email alerts
|

A Mitochondria-Targeted Phenylbutyric Acid Prodrug Confers Drastically Improved Anticancer Activities

Abstract: Phenylbutyric acid (PBA) has been reported as a dual inhibitor of pyruvate dehydrogenase kinases (PDKs) and histone deacetylases (HDACs), exhibiting anticancer effects. However, the low membrane permeability and poor cellular uptake limit its access to the target organelle, resulting in weak potencies against the intended targets. Herein, we report the design and identification of a novel 4-CF3-phenyl triphenylphosphonium-based PBA conjugate (53) with improved in vitro and in vivo anticancer activities. Compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Conversely, excessive ROS production causes oxidative damage to biomolecules and poses detrimental effects on the overall sperm quality (DNA integrity, membrane stability, energy production, motility, capacitation) [42][43][44]. In this study, the increase in the ATP levels was followed by an abnormal increase in ROS after the DCA or 4-PBA treatment similar to studies conducted on cancer cells [45][46][47]. Interestingly, Zhao et al [48] found that DCA can relieve oxidative stress through the PDK2-PDH-Nrf2 channel.…”
Section: Discussionsupporting
confidence: 73%
“…Conversely, excessive ROS production causes oxidative damage to biomolecules and poses detrimental effects on the overall sperm quality (DNA integrity, membrane stability, energy production, motility, capacitation) [42][43][44]. In this study, the increase in the ATP levels was followed by an abnormal increase in ROS after the DCA or 4-PBA treatment similar to studies conducted on cancer cells [45][46][47]. Interestingly, Zhao et al [48] found that DCA can relieve oxidative stress through the PDK2-PDH-Nrf2 channel.…”
Section: Discussionsupporting
confidence: 73%
“…Compound 1 was synthesized as described in the literature [49]. In brief, tris (15 g, 0.124 mol) and SOCl2 (39 mL, 0.519 mol) were placed in a 250 mL flask and stirred at 0 °C.…”
Section: The Synthetic Route Of Compoundmentioning
confidence: 99%
“…Compound 1 was synthesized as described in the literature [49]. In brief, tris (15 g, 0.124 mol) and SOCl 2 (39 mL, 0.519 mol) were placed in a 250 mL flask and stirred at 0 • C. After pyridine (5 mL, 0.062 mol) was added dropwise to the reaction solution, the reaction temperature was raised slowly to 100 °C.…”
Section: Synthesis Of Compound 9 311 the Synthetic Route Of Compoundmentioning
confidence: 99%